Microplastics and gut microbiomes impact on Yunnan snub-nosed monkeys in the Three Parallel Rivers region in China - Xia, Wancai; Zhou, Jiajie; Lu, Zhongwei; Li, Liang; Zhang, Yuan; Fan, Shiyuan; Krzton, Ali; Li, Dayong (Frontiers in Microbiology, 2024)
Background Microplastics (MPs) has been rapidly increasing and interacting with wildlife. As the highest altitudes inhabited non-human primate, Yunnan snub-nosed monkey (Rhinopithecus bieti) have been proven to be an umbrella and flagship species to indicate ecosystem changes and help develop environmental management strategies. In this study, we aimed to investigate the behavioral and ecological reasons for the types, content and differences of MPs in the feces of R. bieti, and explored the effects of MPs on gut microbiome of R. bieti. Methods We used the Agilent 8700 LDIR to identify the abundance and size distribution of MPs in fecal samples, and then analyzed the causes of differences in MPs content by combining data from different populations (wild group, provisioned wild group) and dominance hierarchy. At the same times, the relationships were investigated between gut microbiome diversity and MPs content. Results We first demonstrate MPs ingestion by R. bieti, which highlights the potential impacts of MPs pollution in such high-altitude, inaccessible protected areas. A total of 36 types of MPs were detected, with an average of 75.263 ± 58.141MPs/g. Food provisioning and tourism significantly increased the content of MPs in the feces of R. bieti, but tourism alone did not significantly increase the content of MPs as food provisioning. At the same time, the study found that there was no significant difference in the content of MPs between different sex groups, however, the feces MPs content of adult R. bieti was significantly lower than that of juvenile, and the social dominance hierarchies among OMUs was positively correlated with the exposure of MPs. The current level of MPs pollution did not cause gut microbiome dysbiosis of R. bieti. Conclusion Our study proved from behavioral and ecological perspectives that the R. bieti exposure to MPs was related to provisioned food, and was closely related to dominance hierarchy and age. From the perspective of intestinal microbiology, it was proved that the current intake of MPs did not cause gut microbiome dysbiosis of R. bieti. Our study provided scientific basis for formulating effective protection measures and promoting the effective protection of rare and endangered animals.